Radiation-induced injury and the gut microbiota: insights from a microbial perspective - Qiaoli Wang; Guoqiang Xu; Ouying Yan; Shang Wang; Xin Wang (Therapeutic Advances in Gastroenterology)
Although radiotherapy is the second most effective cancer treatment, radiation injuries limit its use. About 80% of abdominal-pelvic radiotherapy patients develop acute radiation enteritis, with 20% discontinuing radiotherapy. The lack of effective mitigation measures restricts its clinical application. Recent studies have proposed gut microbiota as a potential biomarker for radiation injuries. However, the interaction between gut microbiota and radiation injuries remains poorly understood. This review summarizes two forms of interaction between gut microbiota and radiation injuries based on the location of the radiation field. One type of interaction, referred to as “direct interaction,” involves changes in the diversity and composition of gut microbiota, alterations in microbiota-derived metabolites, disruption of the intestinal barrier, activation of inflammatory responses within the intestine, and involvement of the host’s immune system. The second form, called “indirect interaction,” includes the influence of the gut microbiota on various body systems, such as gut microbiota–brain axis, gut microbiota–cardiopulmonary axis, and gut microbiota–oral axis. Additionally, we examine promising interventions aimed at reshaping the gut microbiota, including the use of probiotics, prebiotics, and fecal microbiota transplantation. The interaction between radiation injuries and gut microbiota is more complex than previously understood. Therefore, further clarification of the underlying mechanisms will facilitate the application of gut microbiota in preventing and alleviating radiation injuries.